Strategies for the Development of Earthenware Craft Business - Khafid Ismail; Sucihatiningsih Dian Wisika Prajanti; Widiyanto Widiyanto (Economics Development Analysis Journal, 2019)
This study aimed to design priorities of strategies for the development of earthenware craft business in Kasongan Tourism Village, Bantul Regency. To pursue this objective, the method used in this study was qualitative descriptive. Moreover, primary and secondary data were used in the data analysis of this study. The primary data were collected from the results of observation result, interviews, documentation, and questionnaires. Meanwhile, the secondary data were obtained from literatures, articles, journals, and internet websites related to the recent study. The technique of analysis used was Analytical Hierarchy Process (AHP). In this study, there were three criteria analyzed using AHP, namely the government policies, human resources, and institution. The results showed that the most prioritized criterion of the strategies for the development of earthenware craft business in Kasongan Tourism Village was the government policies with the weight value of 65 percent. The next criterion was institution with the weight value of 23 percent, and the last prioritized criterion was human resources with the weight value of 12 percent. From the calculation of AHP through expert choice 11 software, it was known that the results of inconsistency ratio was 0.035, meaning that the answers given by the key persons were consistent.